Unboxing the idea of “thinking outside the box”: on the role of creativity in translation training - Puchała-Ladzińska, Karolina (Rzeszów University Press, 2025)
Creativity and innovation involve finding new ways of thinking and organizing ideas. A creative individual is someone who can identify problems and come up with effective solutions. Creative thinking helps adapt to changes in today’s fast-evolving world and it should be applied across all areas of life, including education. By fostering creative thinking, teachers can better prepare students for jobs that currently exist but may be transformed by automation in the future. This is not only relevant for fields like translation, but also areas such as medicine and law, where automation is becoming more prevalent. While certain tasks can be automated, the nature of creativity remains irreplicable. Therefore, those who can creatively develop methods of automating processes will be highly sought after, as will those whose creative abilities enable them to thrive in professions that have not yet emerged. The aim of this paper is to delve deeper into the concept of creativity and its key elements, explore ways it can be stimulated, outline strategies for incorporating creativity-focused tasks in the translation classroom, as well as provide methods for encouraging creative thinking among translation students.
Keywords: creativity; translation classroom; translation teaching; translator training